The in Vitro Inhibitory Effect of Ectromelia Virus Infection on Innate and Adaptive Immune Properties of GM-CSF-Derived Bone Marrow Cells Is Mouse Strain-Independent - Szulc-Dąbrowska, Lidia; Struzik, Justyna; Cymerys, Joanna; Winnicka, Anna; Nowak, Zuzanna; Toka, Felix N.; Gieryńska, Małgorzata (Frontiers in Microbiology, 2017)
Ectromelia virus (ECTV) belongs to the Orthopoxvirus genus of the Poxviridae family and is a natural pathogen of mice. Certain strains of mice are highly susceptible to ECTV infection and develop mousepox, a lethal disease similar to smallpox of humans caused by variola virus (VARV). Currently, the mousepox model is one of the available small animal models for investigating pathogenesis of generalized viral infections. Resistance and susceptibility to ECTV infection in mice are controlled by many genetic factors and are associated with multiple mechanisms of immune response, including preferential polarization of T helper (Th) immune response towards Th1 (protective) or Th2 (non-protective) profile. We hypothesized that viral-induced inhibitory effects on immune properties of conventional dendritic cells (cDCs) are more pronounced in ECTV-susceptible than in resistant mouse strains. To this extent, we confronted the cDCs from resistant (C57BL/6) and susceptible (BALB/c) mice with ECTV, regarding their reactivity and potential to drive T cell responses following infection. Our results showed that in vitro infection of GM-CSF–derived bone marrow cells (GM-BM – comprised of cDCs and macrophages) from C57BL/6 and BALB/c mice similarly down-regulated multiple genes engaged in DC innate and adaptive immune functions, including antigen uptake, processing and presentation, chemokines and cytokines synthesis, and signal transduction. On the contrary, ECTV infection up-regulated Il10 in GM-BM derived from both strains of mice. Moreover, ECTV similarly inhibited surface expression of major histocompatibility complex (MHC) and costimulatory molecules on GM-BM, explaining the inability of the cells to attain full maturation after TLR4 agonist treatment. Additionally, cells from both strains of mice failed to produce cytokines and chemokines engaged in T cell priming and Th1/Th2 polarization after TLR4 stimulation. These data strongly suggest that in vitro modulation of GM-BM innate and adaptive immune functions by ECTV occurs irrespective of whether the mouse strain is susceptible or resistant to infection. Moreover, ECTV limits the GM-BM (including cDCs) capacity to stimulate protective Th1 immune response. We cannot exclude that this may be an important factor in the generation of non-protective Th2 immune response in susceptible BALB/c mice in vivo.